Religión y salud mental - Mureddu Torres, César; Romero Zertuche, Rosa De Gpe. ('Ilu. Revista de Ciencias de las Religiones, 2009)
The authors conceive the religion as a fact. They set out two paths as possible theoretical frameworks studying it, and locate their point of view in the cross of both, showing this chose as an understanding when one takes the religion as subject for several disciplines. The psychological path allows them to expose the Freud’s and Jung’s theories, concluding that the last provides more elements to observe the benefits of religion regarding mental health than the first.
Keywords: Mental health; Analytic Psychology; Religion; Religious feeling; Freudian interpretation; Junguian interpretation